Large Acid-Evoked Currents, Mediated by ASIC1a, Accompany Differentiation in Human Dopaminergic Neurons - Neuhof, Andreas; Tian, Yuemin; Reska, Anna; Falkenburger, Björn H.; Gründer, Stefan (Frontiers in Cellular Neuroscience, 2021)
Acid-sensing ion channels (ASICs) are proton-gated Na+ channels. They contribute to synaptic transmission, neuronal differentiation and neurodegeneration. ASICs have been mainly characterized in neurons from mice or rats and our knowledge of their properties in human neurons is scarce. Here, we functionally characterized ASICs in differentiating LUHMES cells, a human mesencephalic cell line with characteristics of dopaminergic neurons. We find that LUHMES cells express functional ASICs, predominantly homomeric ASIC1a. Expression starts early during differentiation with a striking surge in current amplitude at days 4-6 of differentiation, a time point where – based on published data - LUHMES cells start expressing synaptic markers. Peak ASIC expression therefore coincides with a critical period of LUHMES cell differentiation. It was associated with increased excitability, but not paralleled by an increase in ASIC1 mRNA or protein. In differentiating as well as in terminally differentiated LUHMES cells, ASIC activation by slight acidification elicited large currents, action potentials and a rise in cytosolic Ca2+. Applying the ASIC pore blocker diminazene during differentiation reduced the length of neurites, consistent with the hypothesis that ASIC play a critical role in LUHMES cell differentiation. In summary, our study establishes LUHMES cells as a valuable model to study the role of ASICs for neuronal differentiation and potentially also cell death in a human cell line.